Implementasi Model Experiential Learning dalam Pembelajaran Menulis Teks Miniautobiografi pada Peserta Didik Kelas XII SMK Negeri 10 Surabaya - Safitri, Nawa; Turistiani, Trinil Dwi (GERAM (Gerakan Aktif Menulis), 2025)
Writing skills are an essential aspect of Indonesian language learning for developing critical, reflective, and creative thinking skills. Given the low level of writing skills among Year 12 vocational school students in writing mini-autobiographies, this quantitative research (quasi-experiment) tested the effectiveness of the Experiential Learning model. The results of the study show that the implementation of learning activities reached an optimal level (educators 100%, students 99.1%). There was a significant increase in students' writing skills, from the ‘fair’ category to “good”, with student responses in the ‘very good’ category. These findings confirm that Experiential Learning is effective in improving students' reflective writing skills and active engagement, making it suitable for implementation as a contextual learning strategy.